2012
DOI: 10.1037/a0027496
|View full text |Cite
|
Sign up to set email alerts
|

Expression of direct anger and hostility predict depression symptoms in formerly depressed women.

Abstract: The focus of this two-part study was on distinguishing maladaptive expressions of anger (hostility) from adaptive forms (direct anger). Observational codes assessing the dimensions of hostility and direct anger were developed and applied to a videotaped task in which women discussed a conflictual topic with their romantic partners. Scales showed acceptable interrater reliability and convergent and discriminant validity. In a preliminary test of the predictive validity of these scales, their distinct roles in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…In general, most studies confirm the relationship between hostility and related constructs and depression (Heponiemi et al, 2006;Mao et al, 2003;Rude, Chrisman, Burton Denmark, & Maestas, 2012;Stewart et al, 2010) and anxiety (Vandervort, 1995). In addition, social anxiety correlates positively with hostile feelings toward others, even after controlling for depression (DeWall, Buckner, Lambert, Cohen, & Fincham, 2010).…”
Section: Hostility/anger and Adjustmentmentioning
confidence: 87%
“…In general, most studies confirm the relationship between hostility and related constructs and depression (Heponiemi et al, 2006;Mao et al, 2003;Rude, Chrisman, Burton Denmark, & Maestas, 2012;Stewart et al, 2010) and anxiety (Vandervort, 1995). In addition, social anxiety correlates positively with hostile feelings toward others, even after controlling for depression (DeWall, Buckner, Lambert, Cohen, & Fincham, 2010).…”
Section: Hostility/anger and Adjustmentmentioning
confidence: 87%
“…In the first representation, papers clearly characterized anger as a distinct construct from postnatal depression; 37,39,40,42 in the second representation, studies treated anger as a symptom of postnatal depression. 49,50 Luutonen argued that the Freudian view that depression is anger turned inward is overly simplistic because depressed individuals also express anger and hostility outwardly. Empirical study has demonstrated a modest correlation between anger and depression with depressed persons scoring higher on anger measures than nondepressed persons.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Researchers have also noted higher levels of anger and hostility in individuals who have recovered from depression than those without depression. 49,50 Luutonen argued that the Freudian view that depression is anger turned inward is overly simplistic because depressed individuals also express anger and hostility outwardly. 51 Some authors have speculated that anger motivates action to make changes, serving to mitigate depression; 9,10 however, it is possible that repeated and failed attempts to change one's situation (e.g., failure to get support from others) could lead to chronic or persistent anger and/or depression.…”
Section: Discussionmentioning
confidence: 99%
“…los resultados obtenidos en el cDH tenían alta concordancia con los obtenidos en la entrevista MiNi, usada como prueba de oro debido a su valor predictivo del 75% y grado de sensibilidad y especificidad del 85% (American psyquiatryc association, 2001;pinnintim et al, 2003); pero dicha relación no se mantiene para los casos más severos, probablemente porque los procesos evaluativos resultan ser más complejos debido a la riqueza de los síntomas y solo a través del uso de técnicas de heteroevaluación como la entrevistas diagnosticas MiNi es posible recabar información más completas acerca del caso.…”
Section: Discusión Y Conclusionesunclassified